1992
DOI: 10.1002/ajim.4700210212
|View full text |Cite
|
Sign up to set email alerts
|

A study of the cardiac effects of bromochlorodifluoromethane (Halon 1211) exposure during exercise

Abstract: Bromochlorodifluoromethane (halon 1211, a fire extinguisher), like other fluorocarbons, has been linked with ventricular arrhythmias and myocardial depression. Ten healthy firefighters, aged 40-50, were exposed to 1,000 ppm halon while exercising, in a double-blind, placebo-controlled crossover experiment, and were monitored during and after exposure. Complex ectopy (ventricular couplets and idioventricular rhythm) occurred in two subjects with halon, but none with placebo. One subject had 49.5 ventricular pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…To prevent subjective response bias of the questionnaires, we only showed the summary results of laboratory tests in the Table 2 and test for the dose–response trend. Although the respiratory symptoms of exposed residents were consistent with those in previous reports of Halon exposure (Brooks et al 1985; De La Hoz 1999; Holness and House 1992; Kaufman et al 1992), we wondered why there were decreases in RBC and HB.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…To prevent subjective response bias of the questionnaires, we only showed the summary results of laboratory tests in the Table 2 and test for the dose–response trend. Although the respiratory symptoms of exposed residents were consistent with those in previous reports of Halon exposure (Brooks et al 1985; De La Hoz 1999; Holness and House 1992; Kaufman et al 1992), we wondered why there were decreases in RBC and HB.…”
Section: Discussionsupporting
confidence: 77%
“…Although acute exposure to Halon gases or CFC-12 has been reported to produce central nervous system symptoms [De La Hoz 1999; Harrison et al 1982; Holness and House 1992; World Health Organization (WHO) 1990], respiratory tract symptoms (Brooks et al 1985; De La Hoz 1999; Holness and House 1992; Kaufman et al 1992), and cardiac arrhythmias (Holness and House 1992; Kaufman et al 1992; Mullin et al 1985), there have been no reports of hematologic changes related to these mixed fire extinguishants.…”
Section: Case Presentationmentioning
confidence: 99%
“…First, we characterized the method and evaluated the cellular responses to a set of compounds including 10 wellcharacterized neuroactive agents and 22 reported neurotoxic substances. To test the feasibility of this approach to identify and prioritize chemicals according to their relative neurotoxicity, we next screened a diverse selection of 87 chemicals that contain representative examples of compounds from various environmentally relevant and potentially neurotoxic groups, including pesticides (Shafer and Meyer, 2004;Soderlund et al, 2002), brominated and organophosphorus flame retardants (Dingemans et al, 2011;Hendriks and Westerink, 2015), and polycyclic aromatic hydrocarbons (PAHs) (Kaufman et al, 1992;Zafiropoulos et al, 2014;Zhang et al, 2013). Using techniques previously developed to characterize alterations in spontaneous calcium oscillations (Grimm et al, 2015;Sirenko et al, 2017), we applied a multi-parametric quantification approach to evaluate concentration-dependent effects of these diverse chemicals on neuronal physiology.…”
mentioning
confidence: 99%
“…1 The acute toxicity of CBrClF 2 is usually considered to be related to central nervous system dysfunction 2 and cardiac sensitisation to catecholamines with lowering of the threshold for arrhythmia. 3 Human exposure studies suggest that fluorocarbons can cause respiratory irritation. 4 5 Some authors have reported respiratory irritant effects or reactive airways dysfunction syndrome (RADS) following accidental exposure to bromotrifluoromethane (Halon 1301) 6 7 or thermal degradation products of Freons.…”
mentioning
confidence: 99%